2017
DOI: 10.1093/treephys/tpx105
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi and foliar phosphorus inorganic supply alleviate salt stress effects in physiological attributes, but only arbuscular mycorrhizal fungi increase biomass in woody species of a semiarid environment

Abstract: Salinity may limit plant growth especially in arid and semiarid regions. Arbuscular mycorrhizal fungi (AMF) and the supply of inorganic phosphorus (Pi) could alleviate the negative effects of such stress by improvement in stomatal conductance, photosynthesis and biomass. The aim of this study is to evaluate the ecophysiological performance of Cenostigma pyramidale (Tul.) E. Gagnon & G. P. Lewis (Fabaceae) in a greenhouse under salinity conditions in combination with the supply of AMF and leaf Pi. The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 56 publications
3
32
0
Order By: Relevance
“…Macronutrients, especially P, N, and K, are of vital importance in the growth of plants. Numerous studies have reported that AMF increased nutrient (P, N, K) uptake by various plant species under particular conditions [23,28,29]. Mycorrhizae create links between roots and the soil, with the fungal hyphae being functionally analogous to fine root hairs, and acquire nutrients (especially relatively immobile elements such as P) by altering the uptake dynamics, whereas mycelia extend the effective absorption surfaces of plant roots [30].…”
Section: Discussionmentioning
confidence: 99%
“…Macronutrients, especially P, N, and K, are of vital importance in the growth of plants. Numerous studies have reported that AMF increased nutrient (P, N, K) uptake by various plant species under particular conditions [23,28,29]. Mycorrhizae create links between roots and the soil, with the fungal hyphae being functionally analogous to fine root hairs, and acquire nutrients (especially relatively immobile elements such as P) by altering the uptake dynamics, whereas mycelia extend the effective absorption surfaces of plant roots [30].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the g s of the adaxial and abaxial leaf surfaces in the AM wheat plants was higher than in non-AM plants. AM plants often show higher g s than non-AM plants under unstressed conditions, elevated CO 2 concentration and salt stress (Aroca et al, 2013 ; Goicoechea et al, 2014 ; AugĂ© et al, 2016 ; Frosi et al, 2018 ). A meta-analysis by AugĂ© et al ( 2015 ) indicated that the g s in AM plants was increased by an average of 24% compared with non-AM plants for sufficiently watered and drought-stressed plants.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that AMF influences the stomatal behavior of leaves exposed to salinity stress or elevated CO 2 regime. Under salinity stress, AM plants showed higher g s and lower intercellular CO 2 concentration and water potential, hereby maintaining a favorable gas exchange capacity and water use efficiency (Sheng et al, 2008 ; Evelin et al, 2009 ; Kapoor et al, 2013 ; Frosi et al, 2018 ). At elevated CO 2 , the response of g s to AM symbiosis varies.…”
Section: Introductionmentioning
confidence: 99%
“…Our research showed that the enhanced nutrient absorption observed with AMF inoculation was manifested in the N, P and K contents. Many researchers hold the opinion that the improvement of plant P acquisition is the most important mechanism in mycorrhizal plants under salt stress [42], such as Frosi et al [43] found that P can be transported into the root via protoplasmic circulation, greatly reducing the transport resistance and increasing the transport speed for the continuous mycelium of AMF. However, some other studies found that even if mycorrhizal and nonmycorrhizal plants have a similar P status under unstressed conditions, mycorrhizal plants still grow better than nonmycorrhizal plants under salt stress [44].…”
Section: Plos Onementioning
confidence: 99%